Pengaruh Media Pembelajaran ICT Wordwall Terhadap Hasil Belajar IPAS Pada Materi Berkenalan Dengan Energi Di Kelas III SDN Cengklik Surakarta - Anghelica, Shilvia Mareta; Handini, Oktiana; Restuningsih, Ani (Jurnal Gentala Pendidikan Dasar, 2025)
The purpose of this study was to determine the effect of ICT Wordwall learning media on student learning outcomes in the Natural and Social Sciences (IPAS) subject, "Introducing Energy," in third-grade students at SDN Cengklik Surakarta. This study used a quantitative method with an experimental research design. The population was all third-grade students at SDN Cengklik Surakarta. The instrument used to measure learning outcomes was a multiple-choice test validated by material experts and evaluation experts. Data analysis used a paired sample t-test to determine differences in learning outcomes. The analysis showed a significant difference between the learning outcomes of students using Wordwall and those using conventional learning. The average learning outcomes of the experimental class were higher than those of the control class. From these results, it can be concluded that the use of ICT Wordwall learning media significantly improved student learning outcomes in the "Introducing Energy" topic in third-grade students at SDN Cengklik Surakarta. Wordwall media can be an effective and engaging alternative in the IPAS learning process at the elementary school level.